New girl in Little Cove - Monaghan, Damhnait (Graydon House, 2021)
"After the local French teacher scandalizes the fishing village of Little Cove, Newfoundland, by running off with a priest, the school looks to the mainland to fill the job quickly. They want someone who can uphold their Catholic values and keep a motley group of largely unwilling students in line. The position is filled by mainlander Rachel O'Brien--technically a Catholic (baptized!), technically a teacher (honors degree!)--who's desperate to leave her current mess of a life behind. She isn't surprised that her students don't see the value of learning French. But she is surprised that she can barely understand their English... Is it a compliment or insult to be called a sleeveen? (Insult.) And the anonymous notes left on her car, telling her to go home, certainly don't help to make her feel welcome. Still, she is quickly drawn into the island's traditional music and culture, and into the personal lives of her crusty but softhearted landlady, Lucille, her reluctant students and her fellow teacher Doug Bishop. But when her beliefs clash with church and community, she makes a decision that throws her career into jeopardy. In trying to help a student, has she gone too far? Full of warmth, humor, romance and the quirkiest community of characters..."--Provided by publisher.